A multi-isotope baseline (O, H, C, S, Sr, B, Li, U) to assess leakage processes in the deep aquifers of the Paris basin (France). (August 2021) - Innocent, Christophe; Millot, Romain; Kloppmann, Wolfram
Abstract: Groundwaters from the deep Dogger and Albian aquifers from the Paris Basin in France have been analyzed for oxygen (H2 O and SO4 ), hydrogen (H2 O), carbon, boron, lithium, sulfur (SO4 ), strontium, and uranium isotopes. This study aims to establish a natural hydrogeochemical baseline against which any leak of saline fluids from deeper water masses could be evidenced in case of a hypothetic occurrence of non-conventional exploitation of the hydrocarbons that are present in the underlying Liassic shales. Waters from the Dogger and the Albian aquifers have respectively chloride-alkaline and calcium-bicarbonate geochemical facies, although some waters from the Albian aquifer tend to evolve towards the geochemical characteristics of the waters from the Dogger aquifer. Stable isotopes of the water molecule indicate that waters from the Albian aquifer have a meteoritic origin, whereas saline waters of the Dogger aquifer are mainly influenced by primary and secondary brine inflow from the Triassic evaporitic deposits, and also by diffusive exchanges with the porewaters of the Liassic shales (Bensenouci et al., 2010 ). Carbon isotopes display δ 13 C values that are much higher (>0‰) in waters from the Dogger aquifer waters than those from the Albian (≤- 9‰). Oxygen and sulfur isotopes of dissolved sulfates measured in the waters from the Dogger indicate that sulfur comes probably from the Triassic evaporites, whose signatures are overprinted by bacterial sulfate reduction. The water from the Pantin well near Paris displays isotopic characteristics that are comparable to the saline waters from the Dogger. On the other hand, dissolved sulfates of the other waters from the Albian indicate two different sources: sulfates derived from sulfides that have undergone abiotic oxidation processes, and atmospheric and/or crustal sources. Uranium activity ratios are very high in most groundwaters from the Albian, especially northwest of the Paris region where ratios as high as 20 have been measured. These activity ratios are in most cases higher than those of the saline waters from the Dogger, and suggest important water/rock interaction processes within the Albian aquifer in agreement with Li isotopes data. Boron and strontium isotopic data suggest that some waters from the Albian record the geochemical influence of saline waters comparable to those of underlying aquifers of the Paris Basin, especially Northeast of Paris, in agreement with recent geophysical studies. In the present work, we critically evaluate the information that can be derived from each of the tested isotope systematics in terms of leakage and mixing processes as might occur as the result of man-induced hydraulic shortcuts or changes in the pressure gradients between deep groundwater levels. Sulfur, oxygen, strontium and boron reveal the most sensitive indicators of mixing processes, whereas lithium and, in particular, uranium isotope ratios are strongly overprinted by water-rock interaction and redox processes. Highlights: O, H, C, B, Li, S, Sr and U isotopes are measured in deep waters of the Paris Basin. This study aims to establish a natural hydrogeochemical baseline. Some Albian waters are isotopically comparable to the Dogger saline waters. S, O, Sr and B isotopes are the most sensitive indicators of mixing processes. Li and U isotopes are overprinted by water-rock interaction and redox processes.